THE PRINCIPLE OF NON-SELF-INCRIMINATION IN APPROACHES FOR DRUNKENNESS WHEN DRIVING MOTOR VEHICLES (CIPEEX, 2025)
This study aims to examine the principle of non-self-incrimination, encapsulated in the Latin maxim nemo tenetur se detegere, and its connection with the means of proving intoxication in the context of drunk driving offenses. The principle of non-self-incrimination emerged from the need to overcome inhumane methods of obtaining confessions and establishes that no individual is compelled to provide evidence against themselves. The high number of fatalities resulting from alcohol-impaired driving led the legislature to take action through Laws No. 11,705/2008 and No. 12,760/2012, which intensified penalties for intoxicated drivers. This paper analyzes the legislative progress in the criminal treatment of drunk driving offenses. Additionally, it investigates the appropriate means of proving intoxication in criminal cases, particularly those requiring the defendant's cooperation. The relevance of this study lies in the need to efficiently combat drunk driving while reconciling the State’s jus puniendi with fundamental rights and guarantees, particularly concerning the nemo tenetur se detegere principle and evidence production. The research adopts a qualitative bibliographic methodology, drawing on legal doctrine, jurisprudence, and legislation related to the topic.
Keywords: Traffic offense; Fundamental rights; Drunk driving; Nemo tenetur se detegere; Principle of non-self-incrimination